Temperature-dependent bandgap of (In,Ga)As via P5Grand: A Python Package for Property Prediction of Pseudobinary systems using Grand canonical ensemble - Han, Gyuseung; Yeu, In Won; Ye, Kun Hee; Yoon, Seungjae; Jeong, Taeyoung; Lee, Seung-Cheol; Hwang, Cheol Seong; Choi, Jung-Hae (Chemical physics letters, 2022)
[Display omitted] •P5Grand, a program for calculating the properties of pseudobinary systems, is introduced.•Grand canonical partition function is efficiently calculated using P5Grand.•(In,Ga)As bandgap is predicted using P5Grand from both DFT and cluster expansion results.•Comparison of experimental and predicted bandgap confirms the reliability of P5Grand. We introduce introduces an open-source program for calculating the properties of solid solutions, “Python Package for Property Prediction of Pseudobinary systems using Grand canonical ensemble” (P5Grand). P5Grand uses two main strategies to improve calculation efficiency: random configuration sampling and separate calculations of the strain energy induced by local compositional fluctuations within the grand canonical ensemble. P5Grand can efficiently calculate thermodynamic properties and any properties of interest for arbitrary solid solution as a function of temperature and composition using two input files. The efficiency of P5Grand is demonstrated by the bandgap prediction of (In,Ga)As.